LEVEL OF NATURAL RADIONUCLIDES IN ANIMAL FEED BY GAMMA –RAY SPECTROMETRY - Aleksandra ANGJELESKA, Dimitar NAKOV, Metodija TRAJCHEV, Srecko GJORGJIEVSKI, Radmila CRCEVA-NIKOLOVSKA, Elizabeta DIMITRIESKASTOJKOVIK (University of East Sarajevo, Faculty of Agriculture, Republic of Srpska, Bosnia, 2018)
The radionuclides’ presence in animal feed is due both to natural radioactivity and radioactive pollution from different sources. Controls of radionuclides in animal feed will reduce the risk of radioactive hazards to animal and human health. The study was carried out in order to detect the natural radioactivity in animal feed and feed additive. Gamma spectrometer Canberra Packard with a high-purity germanium detector and Marinelli beakers (1 l capacity) were used for the samples measurement. The most prominent gamma energies observed in the spectra belonged to the naturally occurring radionuclides 40K, 226Ra and 232Th. Other radionuclides if present occurred infrequently at low activity concentration under the measurable level. The results show that 40K had the largest contribution to the specific radioactivity in all the samples. The mean activity concentration of the 40K was highest in feed additive mono calcium phosphate (245.03±17.778 Bq/kg) and lowest activity concentration of the 40K was measured in concentrate feed for dairy cows (23.20±2.626 Bq/kg). The average activity of the other two detected natural radionuclides in feed samples was lowest and ranged from 0.42 to 5.81 Bq/kg for 226Ra and from 0.61 to 2.55 Bq/kg for 232Th. The data analysis using ANOVA showed statistical significant differences in the radioactivity concentration of 40K, 226Ra and 232Th between feed samples (p<0.001).
Keywords: gamma spectrometry, feeds, natural radioactivity